Differences in the theory and practice of the collection management of the Huallamarca site Museum - Hopkins Barriga, Aránzazu (2019)
It reflects on the difference between theory and practice in the management of collections of a site museum (Huallamarca, Miraflores, Lima). Explore the relationship between institution, environment and society. Deliberates on management and Planning, the methods and processes of projection that conform to the reality and the particular context of the site museum location, which involves the society spreading culture through its collections and dialogue as a strategy Paramount to achieve it. The results of this strategy promote knowledge about the protection of the movable and immovable property that underpin the museum. It presents three cases that support the rethinking of the management plan; Strategies to improve the relationship: Museum, archaeological Monument and environment; Future plans and how a site museum can use the tools of the new museology to rethink the exposure of the results of the investigations.